Essential Medicines for Beni, Democratic Republic of the Congo - Falkenhausen, Thomas; Warren, Abbey; Green, Darius; Kolb, Marlie (My University, 2020)
Beni is a city in the northeastern Democratic Republic of the Congo. Currently Congo is suffering from civil unrest, including Beni, which was attacked by the ISIL in 2019. One of the major health issues currently impacting Beni is Ebola. Malaria is also the source of the most deaths in the DRC in a year, with other major illnesses including Cholera, Diphtheria, African Sleeping Sickness, and respiratory illnesses. Due to the geographic location of Beni and its impoverished status, several groups from the WHO’s list of essential medicines were thrown out after being deemed a low priority for combating disease in Beni, these categories were Diuretics, Peritoneal Dialysis, Eye Preparations, Diagnostic Agents, Medicines for mental and behavioral health, and medicines for diseases of joints. Using the WHO list of Essential medicines as a base, 50 medications were chosen to combat the major illnesses facing Beni. Along with drugs, vaccines and supportive care and antiseptics were also chosen. Supportive care is an important combative for diarrhea and hemorrhagic fevers, while antiseptics are important to have in a country that could prove lacking in clean medical facilities.